Evaluation of the Vitros® Anti-T. cruzi assay for its incorporation into the Trypanosoma cruzi infection diagnostic algorithm - Miriam Campos-Ruiz; Jun Hao Wang-Wang; Belén Rivaya; Beatriz Rodriguez-Ponga; Noelia López; Victoria González; Pere-Joan Cardona; Gema Fernández-Rivas (Heliyon)
Background and objective: Serological screening for Chagas disease (CD) in Latin American adults living in Europe is a cost-effective strategy for transmission prevention. The World Health Organization recommends two different serological tests including native and recombinant antigens for IgG detection. In Spain, most commercialized native tests require manual processing. We aimed to evaluate the sensitivity and specificity of the automated Vitros® Anti-T. cruzi native antigen-based test. Methods: A total of 556 serum samples were tested using two different tests: 1) our reference assay, a chemiluminescence immunoassay employing a recombinant multi-antigen protein (Liaison® XL Murex Chagas); 2) a chemiluminescence immunoassay with native antigen (Vitros® Anti-T. cruzi assay). Additionally, 180 samples were also processed by a manual indirect immunofluorescent assay (Chagas IFA). Sensibility, specificity and kappa index were calculated. Results: Vitros® showed a kappa index of 0.94 (IC 95 %: 0.86–1.03) compared to Liaison® XL with a sensitivity of 93.6 % and specificity of 99.5 %. Compared to IFA, Vitros® showed a kappa index of 0.61 (IC 95 %: 0.47–0.76), sensitivity of 97.5 % and specificity of 70.37 %. Discrepant results were obtained mainly in treated patients. Conclusions: The Vitros® Anti-T. cruzi assay showed potential for implementation as an automated serological screening test, enhancing the diagnostic process in high-throughput microbiology laboratories.